The impact of endometriosis on dietary choices and activities of everyday life: a cross-sectional study - Mazza, Elisa; Troiano, Ersilia; Mazza, Santino; Ferro, Yvelise; Abbinante, Antonia; Agneta, Maria Teresa; Montalcini, Tiziana; Pujia, Arturo (Frontiers in Nutrition, 2023)
Endometriosis is characterized by ectopic endometrial tissue and severe pain; frequently, women afflicted by this condition resort to non-medical interventions, such as dietary modifications. The aim of this study is to assess the impact of endometriosis on dietary patterns and quality of life.Methods: An online survey was conducted among Italian women with endometriosis to gather selfreported demographic, clinical, dietary habit, and daily life data post-diagnosis.Results: A total of 4078 participants were included. Following an endometriosis diagnosis, 66% reported changes in eating habits, and 92% experienced a decline in daily life. Respondents chose dietary interventions: gluten-free (15%), anti-inflammatory (8%), Mediterranean (7.1%), or ketogenic (4%) diets, to improve health and reduce symptoms. The study revealed a shift in eating habits, with increased consumption of vegetables, fruits (10%), cereals, legumes (6.6%), and fish (4.5%), while reducing dairy products (18.4%), soy-containing foods (6.7%), and high saturated fats (8%). Eating habit changes correlated with endometriosis stages and worsened daily life. Educational level, endometriosis stages, years of symptoms, and eating habit changes linked to changes in daily life. This is a provisional file, not the final typeset article Conclusions: Our findings emphasize the importance of monitoring eating behaviors to prevent unhealthy habits and malnutrition in women with endometriosis. Further studies are needed to evaluate how different diets impact symptoms and enhance daily life for these individuals.